MODELLING OF PYROLYSIS YIELDS OF PISTACHIO SHELLS BY USING VARIOUS EXPERIMENTAL DESIGN METHODS - Acikalin, Korkut; Bolat, Esen (YILDIZ TECHNICAL UNIV, 2011)
In this study, pyrolysis yields of a biomass waste material, namely pistachio nut shells, were modeled by using various experimental design methods. Box-Behnken and 3(n) Factorial Design were the chosen experimental design methods to investigate. Temperature, reaction time and sweeping gas flowrate were the factors whose effects on total conversion and liquid yields were studied in the ranges of 350-650 degrees C, 10-50 min. and 50-450 ml/min., respectively. The models obtained were compared by using both statistical approaches and controlling experiments which were not involved to derive models. The results showed that the models derived from 3(n) Factorial Design are the most accurate models in the studied ranges.
Keywords: Biomass waste material; experimental design; pyrolysis; Engineering